Characterization of Polymers by NMR and IR Studies (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Because of the increasing interest in nano composites, the molecular characterization of these materials is important to understand the new materials and the property of the new material. The spectroscopic technicians who provide information are immensely indispensable to the characterization of polymers, fillers and compounds at the molecular level. Selected examples for fluorescence spectroscopy, the use of magnetic laughter nuclear (NMR) in solid state, infrared and Raman spectroscopy, the potential of these techniques for surface load analysis, the state of charge distribution in the matrix or host, and the degree of interaction with the polymer and dynamics.